Innovative AI-Based Digital Learning through E-Books and Videos: A Strategy to Support the Merdeka Curriculum in Primary Schools - Arik Kurniawati; Puji Rahayu Ningsih; Aminah Dewi Rahmawati (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This project aims to enhance teachers' ability to use AI-based digital learning media, such as videos and digital books, to implement the Merdeka Curriculum in elementary schools. Participatory action research was used as the research method, and the activities were implemented at SDIT Ulil Albab Kamal Bangkalan in the form of initial observations, training sessions, project facilitation, and evaluations. The result of the pre-training survey showed that most of the teachers were unfamiliar with how AI can be relevant to education materials. Training increased the knowledge and skills of teachers, as evidenced by their ability to create innovative, curriculum-based teaching videos and digital books with interactive content. This study demonstrates that incorporating AI into teacher preparation enhances teaching quality and reinforces teachers' roles as 21st-century learning facilitators.